1984
DOI: 10.3109/10826088409057189
|View full text |Cite
|
Sign up to set email alerts
|

Paraprofessional Versus Professional Drug Counselors: The Progress of Clients in Treatment

Abstract: The progress in treatment of 302 methadone maintenance and drug-free outpatient clients was examined as a function of the background of their 82 counselors. Counselors were either ex-addict paraprofessionals (EXAs), non-ex-addict paraprofessionals (NEAs), or degreed professional counselors (PROs). Client progress was assessed in five areas: drug use, criminality, educational activities, employment, and life quality. In the first four areas, status at treatment entry contrasted with that at two subsequent measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…We used therapists with master’s degrees to deliver the BCT treatment package because we could not find bachelor’s-level therapists or state-certified substance abuse treatment providers who had training or appropriately supervised experience in conducting relationship therapies. Although most studies have found few differences between professional and paraprofessional staff in terms of patient outcome (e.g., Aiken, LoSciuto, Ausetts, & Brown, 1984), it is not clear to what extent this factor may have influenced our outcomes. In this study, we were most interested in observing the effects of adding competently delivered BCT to a substance abuse treatment package delivered in community-based treatment programs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We used therapists with master’s degrees to deliver the BCT treatment package because we could not find bachelor’s-level therapists or state-certified substance abuse treatment providers who had training or appropriately supervised experience in conducting relationship therapies. Although most studies have found few differences between professional and paraprofessional staff in terms of patient outcome (e.g., Aiken, LoSciuto, Ausetts, & Brown, 1984), it is not clear to what extent this factor may have influenced our outcomes. In this study, we were most interested in observing the effects of adding competently delivered BCT to a substance abuse treatment package delivered in community-based treatment programs.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we were most interested in observing the effects of adding competently delivered BCT to a substance abuse treatment package delivered in community-based treatment programs. Thus, the alternative of using only master’s-level therapists for the individual-based package, although eliminating the potential confound of having treatments delivered by therapists with different levels of education, would have reduced the external validity of this study because community-based substance abuse treatment programs usually do not employ a high proportion of professional staff to provide direct services (Aiken et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in employment from approximately 29% to almost 47% was found in a sample of clients in methadone maintenance and drug-free outpatient treatment from 30 days before the point of entry to 4-month follow-up (Aiken et al, 1984). There was, however, a great deal of variation in these increases by type of counselor.…”
Section: Employment and Drug Abuse Treatmentmentioning
confidence: 99%
“…There was, however, a great deal of variation in these increases by type of counselor. Employment increased from 29% to 48% for those clients who had been seen by professional counselors, from 30% to 55% for those who had been seen by paraprofessionals who were not ex-addicts, and from 28% to 40% for those who had been seen by paraprofessionals who were ex-addicts (Aiken et al, 1984). None of these increases were found to be significant, but significant differences were found between the time of first client interview and follow-up for all three counselor groups (Aiken et al, 1984).…”
Section: Employment and Drug Abuse Treatmentmentioning
confidence: 99%
“…In particular, the insight into addiction treatment based on personal history was considered to provide these administrators with immediate advantage over those who do not have such experience. While some research has shown that counselors in recovery are perceived as being more compassionate and trustworthy than those without recovery experience (Aiken, LoSciuto, & Aussetts, 1984;Lawson, 1982;LoSciuto, Aiken, & Aussetts, 1984), other studies have shown no difference in performance and client perceptions of empathy between these two groups (Culbreth, 2000;Kirk, Best, & Irwin, 1986). Moreover, there appears to be no difference in treatment outcomes between treatment delivered by counselors with and without recovery experience (Culbreth, 2000;Najavits, Crits-Christoph, Dierberger, 2000;Najavits & Weiss, 1994;Project MATCH Research Group, 1997).…”
Section: Discussionmentioning
confidence: 86%